A study of Talaq Al-Tafwid in Islamic Law and Contemporary Legislations: Should Malaysia follow suit? - Mehmood, Muhammad Ifzal; Abd Malek, Normi (LexisNexis Malaysia, 2019)
When spouses find that their marriage can no longer subsist due to many different reasons, divorce might be one of the reasonable ways out for them. In the case of a man, he may pronounce talaq to his wife, while for a woman there are variety of ways to dissolve the marriage depending on the reasons and circumstances, including khulu’, fasakh and ta’liq. However, these types of divorces require many conditions to be fulfilled and are also time consuming.Talaq al-tafwid, therefore, in some situations, can become another convenient alternative to dissolve the marriage by both man and woman. This article discusses the status of talaqal-tafwid according to Islamic Law and explores whether it is appropriate to be included in the statutes in Malaysia as another alternative way to dissolve the marriage. The research also investigates other jurisdictions which have adopted and implemented talaq al-tafwid ie Pakistan and Singapore.